(untitled) (Applied Biological Research, 2019)
The purpose of this study was to evaluate the antioxidant, oxidative DNA damage and hepatoprotective effects of olive (Olea europaea L.) leaf extract (OLE) on experimental diabetic rats. These effects of OLE were studied using streptozocin-induced diabetic rats. Antioxidant enzyme activities, oxidative DNA damage analysis and protein oxidation were evaluated spectrophotometrically methods. In addition, histological examination of the liver and pancreas was performed routinely with paraffin embedding and staining method. Protein carbonyl level and 8-hydroxy-2’ – deoxyguanosine (8-OHdG) concentration decreased in OLE administrated group compared to diabetic group. Further, OLE treatment significantly increased superoxide dismutase and glutathione peroxidase activities. It was observed that OLE remarkably attenuated degenerative and necrotic changes in liver and pancreatic tissues. Consequently, it appears that OLE strengthens the antioxidant defense system, protects against oxidative DNA damage, and has a hepatoprotective effect on diabetic rats.